Risk of preeclampsia in adolescent primigravidae in a hospital in the Junin region of the Peruvian highlands - Pacheco Ramos, Estefany (2024)
Introduction: Preeclampsia is one of the main causes of morbidity and mortalityin the world and in Peru. The role of adolescent pregnancy in the development ofpreeclampsia is not clear. Objectives: To analyze the risk of preeclampsia in pregnantadolescent primigravidae in a maternal and child hospital in the Peruvian highlands.Methods: Analytical retrospective cohort study. Pregnant women attended between2018 and 2021 at the Hospital Regional Docente Materno Infantil “El Carmen”, inJunín, Peru, were included. A Poisson regression model adjusted for theoretical andepidemiological criteria was used, calculating the relative risk (RR). Results: A totalof 504 primigravidae were included, 35.9% were adolescents aged 10-19 years and64.1% were adults. A non-significant higher incidence of preeclampsia was observedin adolescents (7.2%) than in adult pregnant women (3.4%) (RR 1.77; 95% CI 0.76-4.14;p 0.19). Conclusion: No association was found between adolescent pregnancy andthe development of preeclampsia in a maternal and child hospital in the Peruvianhighlands.